About a long -song “Ariuntenger” (sacred heaven) of the Uzimchin ethnic group (A respect state and ceremonial song) - Altan-Uul, Taogete (Mongolian Journal of Arts and Culture, 2024)
A long-song of the proper ethnic groups which bears a valuable cultural heritage of the Mongolian language and culture, forming the different colors of the Mongolian nationalities is not still revealed on the research level. It is right that the Mongols today live in the globalization era, getting in step with the rapid world technological development. But there is a rick to forget and loose the traditional culture and custom, including a unique cultural heritage of a proper ethnic group. The uzimchins face the risk to forget and loose the traditional culture, no people who sing the state, ceremonial, and religious songs, passed down during many centuries, in their traditional way and know their verse. So we included the respect state and ceremonial long-song “Ariun Tenger” of the uzimchins in the scientific circulation on the basis of the study of the symbol of its melody and verse, recording and noting it from its bearers. It is distinction that the song is first included in the study circulation. Үзэмчиний “Ариун тэнгэр” уртын дууны тухай (Төр, найрын хүндэтгэлийн дуу) Хураангуй: Монгол туургатны доторх олон янзын өнгө төрхийг бүрдүүлж, монгол хэл, соёлын үнэт нандин өвийг дотроо тээсэн тодорхой угсаатнуудын уртын дууг судалгааны түвшинд төдийлөн нээн гаргаж ирээгүй байна. Монголчууд өнөөдөр дэлхий нийтийн техник технологийн хурдтай хөгжилтэй хөл нийлж, даяаршлын эрин зуунтай нэгдэж амьдрах нь зүй ёсны хэрэг болж байна. Гэвч нийгэм даяаршихын хэрээр уламжлалт соёл, ёс заншил, түүний дотор тодорхой угсаатны соёлын үнэт өв мартагдан алдагдах эрсдэл улам бүр тулгарсаар байна. Үзэмчингүүд олон зуун жилийн өмнөөс зохион дуулж өвлөн уламжилж ирсэн төрийн, найрын, шашны дуунуудыг хуучин дэг жаягаар дуулдаг, үгийг нь мэддэг хүнгүй болж, соёлын үнэт өв мартагдан уламжлал нь үгүй болох, алдагдах, өөр угсаатны дуунд уусах зэрэг эрсдэл улам бүр тулгарсаар байна. Тиймээс бид энэхүү сэдвийн хүрээнд үзэмчин төр, найрын, хүндэтгэлийн “Ариун тэнгэр” уртын дууны аялгуу, шүлэг, яруу найргийн утга бэлгэдэл, хэв намбыг судлан, өвлөн уламжлагчдаас тэмдэглэн ноотлон буулгаж, анх судалгааны эргэлтэд оруулсан болно. Түлхүүр үгс: угсаатан, зан заншил, өвлөн уламжлагч, аялгуу, шүлэг яруу найраг